Leachate as a Fertilizer - Prof. Nagare Kanchan. S, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
No one is unaware of the massive volumes of waste produced on a daily basis by human society. All waste produced from household and industrial sources decompose in open spaces throughout the urban waste process. After that, leachate including high quantities of common cat ions, dioxins, heavy metals (such Pb, Ni, Cu, Hg, and organic compounds), Zn, S, NH3, and Cl, as well as common cat ions, is created as a result of the waste's breakdown. The concentration of heavy metals in the leachate is negatively impacting the environment, soil, and vegetation. The goal of this research is to offer an alternative to leachate for its effective usage as fertilizer. This occurs when the material is thrown untreated on soil or in any landfill. This will provide an active, practical solution to India's leachate problem, which at the moment poses a major environmental concern.
Keywords: Heavy Metals; Landfill; Leachate; Trash; Decomposition